Gypsies and Travellers : Empowerment and Inclusion in British Society - Ryder, Andrew (Andrew Richard); Richardson, Joanna, 1972 June 5- (Book collections on Project MUSE., 2012)
"The eviction at Dale Farm in the UK in 2011 brought the conflicting issues relating to Gypsy and Traveller accommodation to the attention of the world's media. However, as the furore surrounding the eviction has died down, the very pressing issues of accommodation need, inequality of access to education, healthcare and employment, and exclusion from British (and European) society is still very much evident. This topical book examines and debates a range of themes facing Gypsies and Travellers in British society, including health, social policy, employment and education. It also looks at the dilemmas faced in representing disadvantaged minority groups in media and political discourse, theories on power, control and justice and the impact of European initiatives on inclusion. Gypsies and Travellers: Empowerment and Inclusion in British Society will be of interest to students, academics, policy makers, practitioners, those working in the media, police, education and health services, and of course to Gypsies and Travellers themselves."--Publisher's website.